SISTEM DAN DINAMIKA SERTA POLA RELASI SOSIAL EKONOMI MASYARAKAT NELAYAN TRADISIONAL: STUDI KUALITATIF DI TERNATE MALUKU UTARA - Andi Tenri Pada Agustang; Alimin Alwi (Universitas Pendidikan Ganesha, 2025)
The most prominent social stratification in fishing communities is stratification based on control of the means of production. Price determination greatly influences the socio-economic conditions of fishing communities. This gap can also be seen in the fishing community in Ternate City. This research aims to describe and analyze the socio-economic activities of fishing communities related to fishing systems, organization, patterns of cooperative relations between fishermen, profit sharing and marketing patterns, and distribution of fishermen's catches. This research method uses phenomenology, which places the meaning of understanding or comprehension of the object itself through interview, observation, and documentation techniques and is analyzed descriptively-qualitatively. Sango Village is a portrait of the life of a traditional fishing community. Several traditional fishermen who live in Sango Village have almost lost their source of income to finance their families' lives, but over time, their economic activities have improved because they still rely on their livelihood as fishermen. To this day, they continue to exist in developing their activities. The fishing systems and tools used by the fishing community in Sango Village are as follows: 1. Coho nyao toma jala (catching fish with nets) 2. Coho Nyao Se Tabadiku (catching fish with bamboo) 3. Hau/Mangail (fishing). Organization and relationship patterns. Collaboration between fishermen includes Punggawa and Juragan. The conclusion is that the social and economic activities of the Sango Village fishing community grow and develop reciprocally with the socio-cultural aspects seen from the sea fishing system. The organization and pattern of cooperation between fishermen for profit sharing and distribution and the fishing equipment fishermen use is still effortless, such as nets, tabadiku, and hau used by the Sango fishing group.